2020
DOI: 10.33448/rsd-v9i10.8232
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antinociceptive effects of kaempferide from the Brazilian green propolis

Abstract: The Brazilian green propolis is produced by Apis mellifera from Baccharis dracunculifolia. Kaempferide, which was isolated from green propolis and B. dracunculifolia is an O-methylated flavonol bearing gastroprotective, anti-allergic and anti-hypertensive activities. Thus, the aim of this study was to evaluate the anti-inflammatory and antinociceptive potentials of kaempferide, as well as its possible toxicological effect on kidney and liver. For that, nociception was assessed by thermal (hargreaves apparatus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
2
0
4
Order By: Relevance
“…También se ha reportado que el ácido epi-ursólico presente en hojas de Cestrum buxifolium produjo efecto analgésico en las pruebas de ácido acético y de cola retirada (Ciangherotti et al, 2019). Más importante aún, es el hecho que varios metabolitos presentes en B. arborea (Kim et al, 2020), ya fueron reportados por su actividad analgésica ((De Melo et al, 2009, Toker et al, 2004, Almeida-Junior et al, 2020. ).…”
Section: Resultados Y Discusión Prueba De áCido Acéticounclassified
See 1 more Smart Citation
“…También se ha reportado que el ácido epi-ursólico presente en hojas de Cestrum buxifolium produjo efecto analgésico en las pruebas de ácido acético y de cola retirada (Ciangherotti et al, 2019). Más importante aún, es el hecho que varios metabolitos presentes en B. arborea (Kim et al, 2020), ya fueron reportados por su actividad analgésica ((De Melo et al, 2009, Toker et al, 2004, Almeida-Junior et al, 2020. ).…”
Section: Resultados Y Discusión Prueba De áCido Acéticounclassified
“…Con base en estudios fitoquímicos (Mattioli et al, 2012;Kim et al, 2020;Algradi et al, 2021) realizados a la especie (Brugmansia arborea) se han encontrado alcaloides tales como: la atropina, hioscina, noratropina (Arteaga de García et al, 1993), hiosciamina y escopolamina (Mattioli et al, 2012), de los que en algunos casos ya se les atribuye una actividad analgésica y antiinflamatoria (Addams & Wang, 2015). Del mismo modo, Kim et al, (2020) determinaron la presencia de flavonoides como kaempferin, kaempferitrin, kaempferol, quercetin, y (+)-aromadendrin; varios de los cuales ya fueron reportados por su efecto antinociceptivo (De Melo et al, 2009, Toker et al, 2004, Almeida-Junior et al, 2020.…”
Section: Introductionunclassified
“…This product, which is originally used to fix and protect honeycombs, has also been recognized for centuries in terms of its biological and pharmacological properties [ 22 , 23 ]. Propolis extracts have been widely used in medicine due to their antiseptic, antimicrobial [ 24 , 25 ], anti-inflammatory, immunomodulatory [ 26 , 27 ], antioxidant [ 28 ], analgesic [ 27 ], antitumoral [ 29 ], and anticancer [ 30 ] properties, as well as wound-healing activities [ 24 , 31 ], among others. Previous studies have demonstrated the efficacy of free-standing BNC films containing standardized propolis extract (EPP-AF ® ), ethanol extract [ 20 ], and EPP-AF ® microemulsions [ 32 ] against Staphylococcus aureus and S. epidermidis bacteria, further confirming the healing effect of these composites on wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products play an important role in the treatment of the most diverse pathologies, since the allopathic substances available on the market have adverse effects, especially when it comes to anti-inflammatory drugs, such as irritation and ulceration in the gastric mucosa [1]. The search for natural substances with biological/pharmaceutical potential has been increasing among the pharmaceutical industries since 1960, being stimulated by the sale of products that are estimated at several billion dollars [2].…”
Section: Introductionmentioning
confidence: 99%